PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS III SDN PONDOK RANJI 02 - Fitria Rosmi; Ananda Febriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is an influence of the Think Pair Share learning model on the creative thinking abilities of third-grade elementary school students. This study was conducted at Pondok Ranji 02 Public Elementary School, with a sample of 71 students. The main problem in this study is the low ability of students to think creatively in learning and the low ability of students to understand the material. This study uses a quantitative method with a Quasi Experimental Design approach. Data collection techniques in this study use observation, tests and documentation. The average results of the N-Gain Score test in the experimental class increased by 0.647 with a medium category, compared to the control class of 0.158 with a low category. The experimental class has an average post-test score of 82.57 and the control class of 60.28 with a difference in the average value of 22.2. The results of the hypothesis test using the T-Independent test obtained a sig. (2-tailed) value of 0.000 < 0.05 with the decision of Ho rejected and H1 accepted. This shows that there is an influence of the Think Pair Share learning model on the creative thinking abilities of third grade elementary school students.